PENGARUH MEDIA BUKU CERITA BERGAMBAR BERMUATAN NILAI KARAKTER UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PADA SISWA KELAS II SD - Delila Sari Batubara (Smart Education, 2026)
Abstract: Reading is a crucial basic skill for elementary school students as it forms the basis for understanding various subjects. However, some second-grade elementary school students still experience reading difficulties, such as not being fluent, not understanding the content, and having a low interest in reading. This study aims to determine the effect of picture storybooks containing character values ​​on the reading ability of second-grade elementary school students. This study used a quantitative approach with a pre-experimental design, a one-group pretest-posttest design. The subjects were 25 second-grade elementary school students. Data collection techniques included reading tests, observation, and documentation. Data were analyzed using normality tests, homogeneity tests, and t-tests. The results showed that the use of picture storybooks containing character values ​​can improve students' reading ability. This is evident in the increase in students' average scores before and after treatment, from 64.8 to 83.2. In addition to improving reading ability, picture storybooks also help instill character values ​​such as discipline, responsibility, cooperation, and honesty in students. Based on the results of the study, it can be concluded that picture storybooks containing character values ​​have a positive and significant effect on the reading ability of second-grade elementary school students. Keywords: picture story books, character values, reading ability, elementary school students Abstrak Kemampuan membaca merupakan keterampilan dasar yang sangat penting bagi siswa sekolah dasar karena menjadi dasar dalam memahami berbagai mata pelajaran. Namun, masih terdapat siswa kelas II SD yang mengalami kesulitan membaca, seperti belum lancar membaca, kurang memahami isi bacaan, dan rendahnya minat membaca. Penelitian ini bertujuan untuk mengetahui pengaruh media buku cerita bergambar bermuatan nilai karakter terhadap kemampuan membaca siswa kelas II SD. Penelitian ini menggunakan pendekatan kuantitatif dengan metode pre-experimental design jenis one group pretest-posttest design. Subjek penelitian berjumlah 25 siswa kelas II SD. Teknik pengumpulan data dilakukan melalui tes membaca, observasi, dan dokumentasi. Data dianalisis menggunakan uji normalitas, uji homogenitas, dan uji t. Hasil penelitian menunjukkan bahwa penggunaan media buku cerita bergambar bermuatan nilai karakter dapat meningkatkan kemampuan membaca siswa. Hal ini terlihat dari peningkatan nilai rata-rata siswa sebelum dan sesudah perlakuan, yaitu dari 64,8 menjadi 83,2. Selain meningkatkan kemampuan membaca, media buku cerita bergambar juga membantu menanamkan nilai karakter seperti disiplin, tanggung jawab, kerja sama, dan kejujuran kepada siswa. Berdasarkan hasil penelitian dapat disimpulkan bahwa media buku cerita bergambar bermuatan nilai karakter berpengaruh positif dan signifikan terhadap kemampuan membaca siswa kelas II SD. Kata kunci: buku cerita bergambar, nilai karakter, kemampuan membaca, siswa sekolah dasar